2011
DOI: 10.1007/s00216-011-4993-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun composite of polypyrrole-polyamide as a micro-solid phase extraction sorbent

Abstract: A micro-solid phase extraction technique was developed using a novel polypyrrole-polyamide nanofiber sheet, fabricated by electrospinning method. The applicability of the new nanofiber sheet was examined as an extracting medium to isolate malathion as a model pesticide from aqueous samples. Solvent desorption was subsequently performed in a microvial, and an aliquot of extractant was injected into gas chromatography-mass spectrometry. Various parameters affecting the electrospinning process including monomer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…than traditional extraction methods such as solid phase extraction (SPE) and solid phase microextraction (SPME) . Bagheri et al prepared smooth and bead‐free PA‐polypyrrole (PPy) nanofibres by the electrospinning technique in a diameter range of 0.5–3 µm and applied them in the pre‐concentration of malathion as an organophosphorus insecticide in aqueous solutions . In this study, a small piece of fibre mat was placed into the malathion solution for 40 min.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…than traditional extraction methods such as solid phase extraction (SPE) and solid phase microextraction (SPME) . Bagheri et al prepared smooth and bead‐free PA‐polypyrrole (PPy) nanofibres by the electrospinning technique in a diameter range of 0.5–3 µm and applied them in the pre‐concentration of malathion as an organophosphorus insecticide in aqueous solutions . In this study, a small piece of fibre mat was placed into the malathion solution for 40 min.…”
Section: Applicationsmentioning
confidence: 99%
“…88 Bagheri et al prepared smooth and bead-free PA-polypyrrole (PPy) nanofibres by the electrospinning technique in a diameter range of 0.5-3 μm and applied them in the pre-concentration of malathion as an organophosphorus insecticide in aqueous solutions. 89 In this study, a small piece of fibre mat was placed into the malathion solution for 40 min. Then, the adsorbed analyte was desorbed using a suitable solvent and was determined by the GC/MS technique.…”
Section: Pre-concentration and Measurement Of Pesticides In Crops Andmentioning
confidence: 99%
“…A flow rate of 1.85 mL/min was employed for the polymer solution pumping. The electrospinning process was carried out for 4 h. Our preliminary experiments revealed that the coating has a rough thickness of 100 mm [13]. After electrospinning, a piece of 0.7 cm  0.7 cm of nanofiber sheet was cut from the collector center part and it was immersed in ethanol to separate the nanofiber sheet from the Al collector.…”
Section: Electrospinning Of Polypyrrole/polyamidementioning
confidence: 99%
“…Also, nanofibers have small interfibrous pore sizes, strong penetrability and interaction with other compounds [6]. These characteristics suit the nanofibrous materials particularly well to be used as membranes or sorbents in a wide range of applications across biomedical and environmental areas, such as submicro particles separation [7], protein purification [8], air cleaning [9] and heavy metal ions [10] and dye removal [11,12], extraction of pesticides [13] and environmental pollutants [14,15], although their full potential in environmental applications has not been comprehensively explored. Since the entrapment of the target molecules by the nanostructured materials is facilitated due to its enhanced surface area, a small amount of nanofibers is expected to be sufficient for the extraction; therefore, the volume of desorption solvent is greatly reduced [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation